Muslim Monasteries? Some Aspects of Religious Culture in Northern Ethiopia - Abbink, Jon (Aethiopica, 2008)
This paper presents some preliminary observations on Sufi Muslim shrines or retreats in the Ethiopian Wällo region, places where local Muslim holy men or ‘saints’ lead the faithful and act as religious mediators and advisors. Some of these retreats of Sufi Muslims have a ‘monastic’ character, and allow males and females a life of reflection and devotion to God. An obvious parallel with Christian monasteries presents itself, referring to a partly shared religious culture. Some reflections on the extent and nature of this similarity are made, and the need for a fresh approach to the study of religion in Ethiopia/Africa, in the context of contemporary debates about religious identity and the hardening of communal boundaries, is underlined.